Wicksell at the Bank of Canada - Kevin Clinton (Queen's University, Department of Economics, 2006)
Wicksell, writing around the start of the 20th century, outlined an approach to monetary policy strikingly similar to the modern approach, of which the Bank of Canada has been a pioneer. Its features include: the overriding objective of price stability (or low inflation); an interest rate instrument controlled by the rates on settlement balances at the central bank; and a policy rule under which the instrument varies in response to deviations from the objective. Wicksell's natural rate of interest has resurfaced as the neutral rate in mainstream macroeconomic models; and his description of the inflation process has parallels in the modern Phillips curve. Moreover, in a mandate for price stability, one can find a logical basis for the independence and accountability of central banks. The paper tries to explain why Wicksell's ideas fell by the wayside for a century, and describes how the Bank of Canada, by pragmatic steps in the 1990s, helped reinvent Wicksell, and install a neo-Wicksellian monetary policy.
Keywords: E42; E52; E58; 330; Wicksell; central bank; monetary policy; Bank of Canada